1998
DOI: 10.1021/ac980184o
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Organotin Compounds in Water, Sediments, and Sewage Sludge Using Perdeuterated Internal Standards, Accelerated Solvent Extraction, and Large-Volume-Injection GC/MS

Abstract: Two new methods for the simultaneous identification and quantification of organotin compounds (OTs) including monobutyltin, dibutyltin, tributyltin, monophenyltin, diphenyltin, triphenyltin, and tricyclohexyltin (TCyT) in natural waters and sediments, respectively, are presented. For water samples, aqueous ethylation followed by liquid−liquid extraction (LLE) or solid-phase extraction and large-volume-injection GC/MS (50−200 μL) were used. For sediment samples, accelerated solvent extraction at 100 °C with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…In the last few years different procedures for the speciation of organotin compounds have been proposed, among which species specific isotope dilution (SSID) is one [10][11]. The use of isotope enriched spike solutions has not only the potential for accurate, precise and simultaneous determination of OTCs but also the evaluation of different extraction and derivatization protocols for the analysis of sediments and biological sample in which species interconversion/decomposition can take place during sample preparation.…”
Section: Species Specific Isotope Dilution (Ssid)mentioning
confidence: 99%
“…In the last few years different procedures for the speciation of organotin compounds have been proposed, among which species specific isotope dilution (SSID) is one [10][11]. The use of isotope enriched spike solutions has not only the potential for accurate, precise and simultaneous determination of OTCs but also the evaluation of different extraction and derivatization protocols for the analysis of sediments and biological sample in which species interconversion/decomposition can take place during sample preparation.…”
Section: Species Specific Isotope Dilution (Ssid)mentioning
confidence: 99%
“…60 Extractions were performed using prolonged stirring, shaking or sonication as well as extraction into organic solvents, 250 but these procedures are long and cumbersome, and were shown to give unsatisfactory recovery and reproducibility, especially for the most polar species, monobutyltin. Recent developments in extraction procedures involving accelerated solvent extraction [251][252][253] supercritical fluid extraction, [254][255][256][257] and especially microwave-assisted extraction 222,258 have drastically reduced extraction time while providing excellent reproducibility and recovery. Openfocused microwave digestion was shown to give excellent results with an effective extraction time of 3 min only, compared to 12 or more hours for mechanical agitation methods.…”
Section: (C) Soil and Sedimentmentioning
confidence: 99%
“…If the label is introduced in the tin atom [94] the excellent sensitivity and multielemental capabilities of ICP-MS might justify marketing an interface between GC and ICP-MS as a complementary technique to GC-MIP-AED for organotin speciation (and for volatile organometallic speciation in general) [3]. A similar effect could be achieved with 13 C or deuterated organotin standards; with these, determination can be achieved by use of conventional quadrupole GC-MS [95], a technique available in most analytical chemistry laboratories which is sufficiently sensitive for the analysis of organotin compounds in solid matrices. Some authors have found that GC-MIP-AED chromatograms for some sediment samples show not only methyl-, butyl-, and phenyltin compounds but also peaks corresponding to minor organotin species [96].…”
Section: Sediment Samplesmentioning
confidence: 99%